Full-degradable plastic functional master batch and preparation method thereof

By combining modified cellulose fibers and mica with polyethylene glycol and polyvinyl alcohol, a fully degradable plastic functional masterbatch was prepared, solving the problems of insufficient performance and environmental pollution of existing degradable plastics, achieving high performance and rapidity The effect of degradation.

CN119119708APending Publication Date: 2024-12-13HUNAN ZHIZHEN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311053586.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The degradability and mechanical properties of existing biodegradable plastics have not yet reached ideal levels, and incineration and landfill methods have caused pollution to the environment.

Method used

Using a combination of 30-50 parts of matrix resin, 40-70 parts of modified filler, 3-5 parts of dispersant, 2-4 parts of plasticizer and 1-3 parts of weathering agent, the cellulose fiber and mica are modified by The composite material is mixed with polyethylene glycol and polyvinyl alcohol to prepare a fully degraded plastic functional masterbatch with good mechanical properties and complete degradability.

Benefits of technology

The prepared plastic masterbatch has good mechanical properties, high and low temperature resistance, corrosion resistance and rapid biodegradability. It completely degrades, will not cause pollution to the environment, and the degradation rate will be significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of plastics, in particular to a full-degradable plastic functional master batch and a preparation method thereof, and the full-degradable plastic functional master batch comprises the following raw materials in parts by weight: 30-50 parts of matrix resin, 40-70 parts of modified filler, 3-5 parts of a dispersing agent, 2-4 parts of a plasticizer and 1-3 parts of a weather-resistant agent. The invention aims to prepare the plastic functional master batch from completely degradable raw materials, and the plastic functional master batch has good mechanical properties, aging resistance and thermal properties, so that a product prepared from the plastic master batch not only has good mechanical properties, but also can be completely degraded and does not cause pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and in particular to a fully degradable plastic functional masterbatch and a preparation method thereof. Background Art

[0003] In order to solve the serious environmental pollution caused by waste plastics, the methods currently used include incineration and landfill. However, most of the products on the market will cause serious secondary pollution to the environment when incinerated, and landfill is prone to land pollution due to the difficulty of plastic degradation. Therefore, in order to solve the pollution problem of plastic waste to the environment, degradable plastics have been widely studied. In terms of degradation mechanism, current research mainly includes photodegradable plastics, biodegradable plastics, photo-oxidative / biodegradable plastics, thermoplastic starch resin degradable plastics, and carbon dioxide-based biodegradable plastics. Among them, degradable plastics are mainly concentrated in starch-filled degradable plastics. Starch-filled plastics are also called biodegradable plastics, which mainly refer to starch as a filler, blended with general-purpose plastics such as PE and PP; the earliest starch-filled plastics used raw starch and general-purpose plastics. With the continuous deepening of research, researchers began to modify starch and blend it with a compatibilizer and a compatibilizer to make a starch masterbatch, and then blend it with general-purpose plastics. The amount of starch added in starch-filled plastics is generally around 30%, and the manufacturing cost is relatively high. Moreover, the starch masterbatch is mixed with plastic and its degradability needs to be further improved. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a fully degradable plastic functional masterbatch and a preparation method thereof, wherein the plastic functional masterbatch is prepared using fully degradable raw materials and has good mechanical properties, aging resistance and thermal properties, so that the products prepared using the plastic masterbatch not only have good mechanical properties, but can also be completely degraded without causing pollution to the environment.

[0005] The present invention solves the above technical problems by the following technical means:

[0006] A fully degradable plastic functional masterbatch comprises the following raw materials in parts by weight: 30-50 parts of base resin, 40-70 parts of modified filler, 3-5 parts of dispersant, 2-4 parts of plasticizer and 1-3 parts of weathering agent.

[0007] Preferably, the masterbatch comprises the following raw materials in parts by weight: 40 parts of base resin, 55 parts of modified filler, 4 parts of dispersant, 3 parts of plasticizer and 2 parts of weathering agent.

[0008] Preferably, the matrix resin includes one or more of polyethylene, polypropylene, polyvinyl chloride, chlorosulfonated polyethylene, polyvinyl alcohol, and polyethylene glycol.

[0009] Preferably, the dispersant is a mixture of stearamide, higher alcohol and paraffin, the plasticizer is a mixture of dimethyl phthalate and butyl benzyl phthalate, and the weathering agent is a mixture of antioxidant 1010 and an anti-ultraviolet agent.

[0010] Preferably, the modified filler comprises the following raw materials: composite cellulose fiber, polyethylene glycol and titanate coupling agent.

[0011] Preferably, the preparation method of the modified filler comprises the following steps:

[0012] S1 pretreatment: the hydromica and cellulose fiber are placed at 40-60°C and baked for 8-24 hours. After baking, the hydromica is crushed, gelatinized starch is added to the crushed hydromica, deionized water is added, and stirred for 1-3 hours. After stirring, the hydromica is filtered and dried to obtain the pretreated hydromica;

[0013] S2 Preparation of composite cellulose fiber: The hydromica treated in step S1 is placed in a planetary ball mill to obtain nano hydromica, and the nano hydromica, cellulose fiber and titanate coupling agent are mixed and placed in a mixer, and stirred at 45 r / min for 3-5 h at 60° C. to obtain composite cellulose fiber after the stirring is completed;

[0014] Preparation of S3 modified filler: Place the composite cellulose fiber prepared in step S2 in an ether solution, add polyethylene glycol 400, stir evenly, add sorbitol solution, precipitate, filter, remove the filtrate to obtain a solid, rinse and dry the solid, place it in a planetary ball mill, and ball mill to obtain a nano-modified filler.

[0015] Hydromica is a ferromagnesian aluminum silicate mineral with excellent properties such as water absorption and expansion, low density, stable chemical properties, heat insulation, antibacterial, fire resistance, and cold resistance. Gelatinized starch is a completely degradable organic matter. Through baking in pretreatment, most of the structural water in hydromica is volatilized, and pores are formed during the volatilization process. Then, the gelatinized starch is mixed with the dried hydromica and placed in deionized water to expand the hydromica, and the gelatinized starch is filled in the hydromica.

[0016] Cellulose fiber is a high-strength and high-modulus fiber with a carbon content of more than 90%. It has the characteristics of high temperature resistance, friction resistance, heat conduction and corrosion resistance. Cellulose fiber has a large specific surface area. By cross-linking nano-hydromica on the cellulose fiber, a double-degradable sandwich structure is formed, so that the composite cellulose fiber has excellent properties such as stable chemical properties, high and low temperature resistance, corrosion resistance, and friction resistance. Hydromica is a natural mineral and cellulose fiber is a natural degradable substance, so that the modified filler can be completely degraded in the soil. During the degradation process, the degradation speed is accelerated due to the effect of gelatinized starch.

[0017] Polyethylene glycol is a high molecular organic compound. Polyethylene glycol resin is a completely degradable resin with excellent lubricity, moisture retention, dispersibility, adhesion, good water solubility, and good compatibility with many organic components, but insoluble in most aliphatic hydrocarbons and ethers. Polyethylene glycol and sorbitol will produce a shrinkage reaction to precipitate polyethylene glycol. By precipitating polyethylene glycol on composite cellulose fibers, polyethylene glycol is cross-linked with the composite cellulose fibers through a titanate coupling agent, thereby improving the degradability, dispersibility and adhesion of the composite cellulose fibers, so that the filler can improve the degradability, mechanical properties and thermal properties of the matrix resin when mixed with the matrix resin.

[0018] Preferably, the mass ratio of the hydromica, cellulose fiber and titanate coupling agent is (3-5): (1-2.5): (0.1-0.8)

[0019] By adjusting the mass ratio of hydromica, cellulose fiber and titanate coupling agent, nano hydromica can be better cross-linked on the cellulose fiber, making the overall performance of the cellulose fiber more uniform.

[0020] Preferably, the cellulose fibers are a mixture of staple cellulose fibers and short-cut cellulose fibers, and the mass ratio of the staple cellulose fibers to the short-cut cellulose fibers is 1:2.3.

[0021] The present application also discloses a method for preparing a fully degradable plastic functional masterbatch, the preparation method being as follows:

[0022] Place the base resin in a high-speed mixer, stir for 30-60 minutes at 110-130°C, add modified filler and dispersant, continue stirring for 20-40 minutes, add plasticizer and continue stirring for 5-10 minutes, add weathering agent, stir for 10-20 minutes, transfer to a screw extruder, set the host temperature to 160-170°C, the mold temperature to 170-190°C, the head temperature to 190-200°C, extrude and shape, cool, pelletize and dry to obtain a masterbatch.

[0023] Preferably, the matrix resin is a mixture of polyethylene, polyethylene glycol and polyvinyl alcohol, and the mass ratio of the polyethylene, polyethylene glycol and polyvinyl alcohol is (1-3.5):(3-5):(2-4.5).

[0024] By selecting the matrix resin, wherein polyethylene is an incompletely degradable resin, and polyethylene glycol and polyvinyl alcohol are completely degradable resins, and by mixing polyethylene, polyethylene glycol and polyvinyl alcohol, the matrix resin can be fully blended with the modified filler when mixed, and then a dispersant is added to make the modified filler fully combined with the matrix resin, so that the prepared plastic masterbatch has good mechanical properties, thermal properties and complete degradability, so that the products prepared from the plastic masterbatch can be biodegraded while being biodegraded by the biological breakdown of polyethylene during degradation, thereby accelerating the degradation rate; by adding a weathering agent, the products prepared from the plastic masterbatch have good weather resistance.

[0025] The present application adopting the above scheme has the following beneficial effects:

[0026] By selecting natural minerals and completely degradable cellulose fibers and base resins for melt extrusion, the prepared plastic masterbatch can be completely degraded. By using cellulose fibers and hydromica as modified reinforcing fillers, the prepared plastic masterbatch has good mechanical properties, high and low temperature resistance, corrosion resistance, and anti-friction properties; through the selection of base resins, when polyethylene is biodegraded, polyvinyl alcohol and polyethylene glycol are biodegraded simultaneously, which accelerates the degradation rate and reduces the impact on the environment. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention:

[0028] Example 1, Preparation of plastic masterbatch

[0029] Preparation of modified fillers

[0030] S1 pretreatment: 40 parts by weight of hydromica and cellulose fiber were placed at 40°C and baked for 24 hours. After baking, the hydromica was crushed, 25 parts by weight of gelatinized starch was added to the crushed hydromica, deionized water was added, and the mixture was stirred at a speed of 40r / min for 3 hours. After stirring, the mixture was filtered and dried at 40°C to obtain pretreated hydromica;

[0031] Preparation of S2 composite cellulose fiber: 20 parts by mass of hydromica treated in step S1 are placed in a planetary ball mill for ball milling to obtain nano hydromica, 20 parts by mass of nano hydromica, 10 parts by mass of cellulose fiber and 0.8 parts by mass of titanate coupling agent are mixed, placed in a blender, stirred at 45 r / min for 3 h at 60° C., and after the stirring is completed, composite cellulose fiber is obtained;

[0032] Preparation of S3 modified filler: Place 10 parts by mass of the composite cellulose fiber prepared in step S2 in 25L of ether solution, add 8 parts by mass of polyethylene glycol 400, stir evenly, add 10 parts by mass of sorbitol solution, precipitate, filter, remove the filtrate to obtain a solid, rinse the solid with deionized water 2-3 times, and dry it at 50°C after rinsing. Place the dried modified filler in a planetary ball mill and ball mill to obtain a nano-modified filler. The particle size of the nano-modified filler is 35nm as measured by instrument.

[0033] Preparation of plastic masterbatch

[0034] 10 parts by mass of polyethylene, 30 parts by mass of polyethylene glycol and 20 parts by mass of polyvinyl alcohol are placed in a high-speed mixer, stirred at 110°C for 60 minutes, 40 parts by mass of modified filler and 3 parts by mass of dispersant are added, stirring is continued for 20 minutes, 2 parts by mass of plasticizer are added and stirring is continued for 5 minutes, 1 part by mass of weathering agent is added and stirred for 10 minutes, and then transferred to a screw extruder, the main engine temperature is set to 160-170°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding is performed, and after cooling, pelletizing and drying, a fully degradable plastic functional masterbatch is obtained.

[0035] Example 2, Preparation of Plastic Masterbatch II

[0036] Preparation of modified fillers

[0037] S1 pretreatment: 55 parts by weight of hydromica and cellulose fiber were placed at 50°C and baked for 16 hours. After baking, the hydromica was crushed, 40 parts by weight of gelatinized starch was added to the crushed hydromica, deionized water was added, and the mixture was stirred at a speed of 60r / min for 2 hours. After stirring, the mixture was filtered and dried at 40°C to obtain pretreated hydromica;

[0038] Preparation of S2 composite cellulose fiber: 30 parts by mass of hydromica treated in step S1 are placed in a planetary ball mill for ball milling to obtain nano hydromica, 30 parts by mass of nano hydromica, 15 parts by mass of cellulose fiber and 1.2 parts by mass of titanate coupling agent are mixed, placed in a blender, stirred at 45 r / min for 4 hours at 60° C., and after the stirring is completed, composite cellulose fiber is obtained;

[0039] Preparation of S3 modified filler: Place 16 parts by mass of the composite cellulose fiber prepared in step S2 in 40L of ether solution, add 12 parts by mass of polyethylene glycol 400, stir evenly, add 15 parts by mass of sorbitol solution, precipitate, filter, remove the filtrate to obtain a solid, rinse the solid with deionized water 2-3 times, and dry it at 50°C after rinsing. Place the dried modified filler in a planetary ball mill and ball mill to obtain a nano-modified filler. The particle size of the nano-modified filler is 38nm as measured by instrument.

[0040] Preparation of plastic masterbatch

[0041] 20 parts by mass of polyethylene, 40 parts by mass of polyethylene glycol and 30 parts by mass of polyvinyl alcohol are placed in a high-speed mixer, stirred at 120°C for 50 minutes, 55 parts by mass of modified filler and 4 parts by mass of dispersant are added, stirring is continued for 30 minutes, 3 parts by mass of plasticizer are added and stirring is continued for 8 minutes, 2 parts by mass of weathering agent are added and stirred for 15 minutes, and then transferred to a screw extruder, the main engine temperature is set to 160-170°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding is performed, and after cooling, pelletizing and drying, a fully degradable plastic functional masterbatch is obtained.

[0042] Example 3, Preparation of plastic masterbatch

[0043] Preparation of modified fillers

[0044] S1 pretreatment: 70 parts by weight of hydromica and cellulose fiber were placed at 60°C and baked for 8 hours. After baking, the hydromica was crushed, 60 parts by weight of gelatinized starch was added to the crushed hydromica, deionized water was added, and the mixture was stirred at a speed of 100 r / min for 1 hour. After stirring, the mixture was filtered and dried at 40°C to obtain pretreated hydromica;

[0045] Preparation of S2 composite cellulose fiber: 40 parts by mass of hydromica treated in step S1 are placed in a planetary ball mill for ball milling to obtain nano hydromica, 40 parts by mass of nano hydromica, 22 parts by mass of cellulose fiber and 2 parts by mass of titanate coupling agent are mixed, placed in a mixer, stirred at 45 r / min for 3 hours at 60° C., and after stirring, composite cellulose fiber is obtained;

[0046] Preparation of S3 modified filler: Place 20 parts by mass of the composite cellulose fiber prepared in step S2 in 45L of ether solution, add 15 parts by mass of polyethylene glycol 400, stir evenly, add 20 parts by mass of sorbitol solution, precipitate, filter, remove the filtrate to obtain a solid, rinse the solid with deionized water 2-3 times, and dry it at 50°C after rinsing. Place the dried modified filler in a planetary ball mill and ball mill to obtain a nano-modified filler. The particle size of the nano-modified filler is 41nm as measured by instrument.

[0047] Preparation of plastic masterbatch

[0048] 35 parts by mass of polyethylene, 50 parts by mass of polyethylene glycol and 45 parts by mass of polyvinyl alcohol are placed in a high-speed mixer, stirred at 130°C for 40 minutes, 70 parts by mass of modified filler and 5 parts by mass of dispersant are added, stirring is continued for 40 minutes, 4 parts by mass of plasticizer are added and stirring is continued for 10 minutes, 3 parts by mass of weathering agent are added and stirred for 20 minutes, and then transferred to a screw extruder, the main engine temperature is set to 160-170°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding is performed, and after cooling, pelletizing and drying, a fully degradable plastic functional masterbatch is obtained.

[0049] Example 4 (Comparative Example 1) Preparation of plastic masterbatch

[0050] In this embodiment, the filler is nano-hydromica with a particle size of 20-50nm.

[0051] 35 parts by mass of polyethylene, 50 parts by mass of polyethylene glycol and 45 parts by mass of polyvinyl alcohol are placed in a high-speed mixer, stirred at 130°C for 40 minutes, 70 parts by mass of nano-hydromica and 5 parts by mass of dispersant are added, stirring is continued for 40 minutes, 4 parts by mass of plasticizer are added and stirring is continued for 10 minutes, 3 parts by mass of weathering agent are added and stirred for 20 minutes, and then transferred to a screw extruder, the main engine temperature is set to 160-170°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding is performed, and after cooling, pelletizing and drying, a fully degradable plastic functional masterbatch is obtained.

[0052] Example 5 (Comparative Example 2) Preparation of Plastic Masterbatch

[0053] In this embodiment, the modified filler is the modified filler prepared in Example 2.

[0054] 50 parts by mass of polyethylene glycol and 45 parts by mass of polyvinyl alcohol are placed in a high-speed mixer, stirred at 130°C for 40 minutes, 70 parts by mass of modified filler and 5 parts by mass of dispersant are added, stirring is continued for 40 minutes, 4 parts by mass of plasticizer are added and stirring is continued for 10 minutes, 3 parts by mass of weathering agent are added and stirred for 20 minutes, and then transferred to a screw extruder, the main engine temperature is set to 160-170°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding is performed, and after cooling, pelletizing and drying, a fully degradable plastic functional masterbatch is obtained.

[0055] The plastic masterbatch prepared in Examples 1-5 was tested for tensile properties, heat resistance, impact resistance, and biodegradation rate, wherein three groups of tensile properties, heat resistance, and impact resistance were tested in parallel, and the average values ​​were taken. The test results are shown in Tables 1 and 2:

[0056] Table 1 Table 2

[0057]

[0058]

[0059] It can be seen from the data in Table 1 and Table 2 that the plastic masterbatches prepared in Examples 1-3 all have good tensile properties, heat resistance and impact strength, among which the various properties of the plastic masterbatch prepared in Example 2 are significantly better than those of other examples, and the biodegradation rate of Example 2 is significantly better than that of Example 1 and Example 3, indicating that the plastic masterbatches prepared in Examples 1-3 can be basically completely degraded within 90 days with a small amount of residue. Compared with ordinary degradable plastics, they are basically completely degraded, and the degradation rate of Example 2 is the fastest.

[0060] It can be seen from the data of Example 2 and Example 4 that the tensile properties, heat resistance and impact strength of Example 2 are better than those of Example 4, and the biodegradation rate of Example 2 is significantly better than that of Example 4, indicating that the addition of modified fillers can increase the biodegradation rate of plastics compared to when only ordinary nano-hydromica fillers are added.

[0061] It can be seen from the data of Example 2 and Example 5 that the tensile properties, heat resistance and impact strength in Example 2 are better than those in Example 5, and the biodegradation rate of Example 2 is significantly better than that of Example 5, indicating that adding a certain amount of polyethylene as a base resin can play a synergistic enhancement role with the modified filler and can further accelerate the biodegradation rate of the plastic.

[0062] It can be seen from Example 2 and the degradation rate of common degradable plastics that the degradation rate of the completely degradable plastic prepared in this scheme is much greater than the degradation rate of common degradable plastics on the market, indicating that the combination of the base resin and the modified filler selected in this scheme can accelerate the degradation of plastics, thereby reducing the pollution of plastics to the environment.

[0063] The above is a detailed introduction to a fully degradable plastic functional masterbatch and a preparation method thereof provided by the present invention. The description of the specific embodiment is only used to help understand the method and core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0064] It should be noted that if no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0065] The above examples are intended to provide a better understanding of the present invention, and are not intended to be limiting of the best implementation mode described herein, nor are they intended to limit the content and protection scope of the present invention. Any product identical or similar to the present invention that is derived by anyone under the inspiration of the present invention or by combining the present invention with features of other prior arts shall fall within the protection scope of the present invention.

Claims

1. A fully degradable plastic functional masterbatch, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of base resin, 40-70 parts of modified filler, 3-5 parts of dispersant, 2-4 parts of plasticizer and 1-3 parts of weathering agent.

2. A fully degradable plastic functional masterbatch according to claim 1, characterized in that: The masterbatch includes the following raw materials in parts by weight: 40 parts of base resin, 55 parts of modified filler, 4 parts of dispersant, 3 parts of plasticizer and 2 parts of weathering agent.

3. A fully degradable plastic functional masterbatch according to claim 1 or 2, characterized in that: The matrix resin includes one or more of polyethylene, polypropylene, polyvinyl chloride, chlorosulfonated polyethylene, polyvinyl alcohol, and polyethylene glycol.

4. The fully degradable plastic functional masterbatch according to claim 1, characterized in that: The dispersant is a mixture of stearamide, higher alcohol and paraffin, the plasticizer is a mixture of dimethyl phthalate and butyl benzyl phthalate, and the weathering agent is a mixture of antioxidant 1010 and an anti-ultraviolet agent.

5. The fully degradable plastic functional masterbatch according to claim 1, characterized in that: The modified filler comprises the following raw materials: composite cellulose fiber, polyethylene glycol and titanate coupling agent.

6. The fully degradable plastic functional masterbatch according to claim 5, characterized in that: The preparation method of the modified filler comprises the following steps: S1 pretreatment: the hydromica and cellulose fiber are placed at 40-60°C and baked for 8-24 hours. After baking, the hydromica is crushed, gelatinized starch is added to the crushed hydromica, deionized water is added, and stirred for 1-3 hours. After stirring, the hydromica is filtered and dried to obtain the pretreated hydromica; S2 Preparation of composite cellulose fiber: The hydromica treated in step S1 is placed in a planetary ball mill to obtain nano hydromica, and the nano hydromica, the dried cellulose fiber and the titanate coupling agent are mixed, placed in a mixer, and stirred at 45 r / min for 3-5 h at 60° C. After the stirring is completed, the composite cellulose fiber is obtained; Preparation of S3 modified filler: Place the composite cellulose fiber prepared in step S2 in an ether solution, add polyethylene glycol 400, stir evenly, add sorbitol solution, precipitate, filter, remove the filtrate to obtain a solid, rinse and dry the solid, place it in a planetary ball mill, and ball mill to obtain a nano-modified filler.

7. A fully degradable plastic functional masterbatch according to claim 6, characterized in that: The mass ratio of the hydromica, cellulose fiber and titanate coupling agent is (3-5): (1-2.5): (0.1-0.8).

8. The fully degradable plastic functional masterbatch according to claim 6, characterized in that: The cellulose fibers are a mixture of short-filament cellulose fibers and short-cut cellulose fibers, and the mass ratio of the short-filament cellulose fibers to the short-cut cellulose fibers is 1:2.

3.

9. A method for preparing a fully degradable plastic functional masterbatch as claimed in claims 1 to 8, characterized in that: The preparation method is as follows: placing a base resin in a high-speed mixer, stirring for 30-60 minutes at 110-130° C., adding a modified filler and a dispersant, continuing to stir for 20-40 minutes, adding a plasticizer and continuing to stir for 5-10 minutes, adding a weathering agent, stirring for 10-20 minutes, transferring to a screw extruder, setting the main engine temperature to 160-170° C., the mold temperature to 170-190° C., the head temperature to 190-200° C., extruding, cooling, pelletizing, and drying to obtain a masterbatch.

10. The method for preparing a fully degradable plastic functional masterbatch according to claim 9, characterized in that: The matrix resin is a mixture of polyethylene, polyethylene glycol and polyvinyl alcohol, and the mass ratio of the polyethylene, polyethylene glycol and polyvinyl alcohol is (1-3.5): (3-5): (2-4.5).